THE EFFECT OF COMPENSATION AND WORK ENVIRONMENT ON PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT THE TUGU HOTEL IN NORTH LOMBOK - Baiq Ertin Helmida; Rosyia Wardani; Hekmatyar Alwi (ShariaBiz International Journal of Economics & Business, 2024)
This study examines the effect of compensation and work environment on employee performance through job satisfaction as an intervening variable at Tugu Hotel North Lombok. The variables in this study consist of 2 independent variables, namely compensation (X1) and work environment (X2); the intervening variable is job satisfaction (Z) and the dependent variable is performance (Y). The population in this study were employees of Tugu Hotel North Lombok. The sample in this study used stratified random sampling, with 60 employees as respondents. The analytical tool used is path analysis. The results showed that (1) compensation directly has an insignificant effect on employee performance; (2) compensation directly has an insignificant effect on employee satisfaction; (3) compensation indirectly has a significant effect on performance through job satisfaction. Thus, job satisfaction mediates the effect of compensation on performance; (4) The work environment directly has a significant effect on employee performance; (5) The work environment directly has a significant effect on employee satisfaction; (6) The work environment indirectly has no significant effect on performance through job satisfaction. Thus, job satisfaction mediates the effect of the work environment on performance; (7) Job satisfaction directly has a significant effect on employee performance.